2020
DOI: 10.7759/cureus.9194
|View full text |Cite
|
Sign up to set email alerts
|

Etiology and Types of Seizures in Patients Presenting to a Tertiary Care Hospital in Karachi: A Cross-Sectional Study

Abstract: Introduction Epilepsy is a burdensome disorder for affected individuals and community. There is limited data available on the epidemiological aspects of seizures in Pakistan and further research is necessary. We aimed to fill this gap by studying this information in epilepsy patients presenting to our neurology department. The purpose of this study is to evaluate the causes and types of seizures among the target population. Method This is a cross-sectional study conducted at the Department of Neurology, Dr. Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“… 11 This is especially alarming as a recent study from our centre found CNS infections as among the most common causes of symptomatic epilepsy in both pediatric and adult age group patients in our set-up. 23 Among the four cases of super refractory SE in this study, three were secondary to CNS infections. The need of the hour is to prevent super-refractory status epilepticus by controlling the risk factors in the population, as mortality rate in these cases ranges from 30 to 50%.…”
Section: Discussionmentioning
confidence: 69%
“… 11 This is especially alarming as a recent study from our centre found CNS infections as among the most common causes of symptomatic epilepsy in both pediatric and adult age group patients in our set-up. 23 Among the four cases of super refractory SE in this study, three were secondary to CNS infections. The need of the hour is to prevent super-refractory status epilepticus by controlling the risk factors in the population, as mortality rate in these cases ranges from 30 to 50%.…”
Section: Discussionmentioning
confidence: 69%
“…This mean age is comparable to 20.0 ± 15.1 years reported by Mukuku et al 3 in Lubumbashi (in DRC). In a Pakistani study, Jawaid et al 11 found a mean age of 21.4 ±3.2 years. In studies in SSA and other developing countries, the mean age of epileptic patients ranges from 15 to 20 years, 12,13 unlike in developed countries where epilepsy has a bimodal distribution (i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Studies in SSA have shown a strong representation of generalized tonic-clonic seizures 3,14 and elsewhere. 11 There is a good identification of generalized tonico-clonic seizures by the casework. Indeed, these seizures are the most dramatic.…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Singh TD et al showed metabolic abnormalities causing 12% of the cases of new onset seizures, in whom hyponatremia was the most common cause. 25 Adults with secondary seizures were diagnosed most often with head injury (25.2%), brain tumors (19.9%) and stroke (18.4%) as causative factors in a study conducted by Wajid J et al 26 Among total number of cases, 8.6% have positive family history of epilepsy while a study conducted in Aziz H et al showed that family history was positive up to 32 %. 27 …”
Section: Discussionmentioning
confidence: 99%